(untitled) (Research, Society and Development, 2021)
The objective of this study was to validate an analytical technique with HPLC-PDA for plasma measurement of carbamazepine (CBZ) and its metabolite carbamazepine-10, 11-epoxide (CBZ-E) for therapeutic monitoring (TM) of patients diagnosed with bipolar disorder (BD), as well as evaluating hematological and biochemical parameters of patients using CBZ. Sixteen patients registered with the Public Service of Psychiatry were selected. CBZ and CBZ-E measurements were performed with HPLC-PDA shimadzu LC-20 AT Prominence, under concentration gradient. Validation criteria: selectivity, linearity, precision, accuracy, recovery, stability. Hematological and biochemical tests were performed using conventional methods. As a result, it was obtained: accuracy >85% and precision <15%, good selectivity, robustness and stability, LOQ = 250 ng.mL-1 and HQL = 60,000 ng.mL-1. Among patients, 25% and 6.25% had CBZ and CBZ-E levels within the therapeutic range, respectively. There were hematological and biochemical changes related to the drug. The validated method is reliable for its intended purpose. TM proved to be extremely useful for detecting therapeutic failure.